Agriculture and climate change: Adaptation to climate change: Household impacts and institutional responses - Yamauchi, Futoshi; Quisumbing, Agnes R. (International Food Policy Research Institute, 2009)
Climate change will bring with it increased frequency of two types of natural disasters that affect agriculture and rural households: droughts and floods. It will also alter rainfall patterns, thereby changing farming practices, household behavior, and welfare. Households all over the world use a variety of formal and informal mechanisms to manage risk and cope with unexpected events that negatively affect incomes, assets, or well-being. These mechanisms include both preparation for and responses to natural disasters. In low-income settings, where formal insurance and government supports are limited, households tend to rely on informal coping strategies, such as transfers from friends and neighbors, remittances, or investments in a diverse range of assets, from livestock to human capital. When disaster-related shock affects only a few households at a time, informal mechanisms can be quite effective in dealing with the situation. However, if the shock affects large areas simultaneously, small-scale coping mechanisms become ineffective. Research on several climate-related national disasters-the 1998 floods in Bangladesh, the 2001 drought in Ethiopia, and the 2001-02 failed maize harvest in Malawi-suggests that the upcoming negotiations in Copenhagen need to explicitly define, support, and expand policies that protect vulnerable populations from the expected increase in climate-change related weather events.